2014
DOI: 10.1038/bjc.2014.604
|View full text |Cite
|
Sign up to set email alerts
|

The tumour hypoxia marker pimonidazole reflects a transcriptional programme associated with aggressive prostate cancer

Abstract: Background:The hypoxia marker pimonidazole is a candidate biomarker of cancer aggressiveness. We investigated the transcriptional programme associated with pimonidazole staining in prostate cancer.Methods:Index tumour biopsies were taken by image guidance from an investigation cohort of 52 patients, where 43 patients received pimonidazole before prostatectomy. Biopsy location within the index tumour was verified for 46 (88%) patients, who were included for gene expression profiling and immunohistochemistry. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 52 publications
5
158
2
1
Order By: Relevance
“…However, although the head and neck cancer signature by Eustace and colleagues identified patients with laryngeal cancer who seemed to benefit from adjuvant hypoxia-modifying treatment, this was not the case when the signature was used on patients with bladder cancer (12). Moreover, when comparing six of the previously published hypoxia gene signatures (10)(11)(12)(13)(14)(15) with the classifier genes in this work, we found that our genes had the strongest prognostic impact in the cervical cancer dataset (Supplementary Document S3). In particular, only the signature developed in breast cancer by Hu and colleagues (15) showed a significant association to outcome (P ¼ 0.026) in Cox PH univariate analysis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, although the head and neck cancer signature by Eustace and colleagues identified patients with laryngeal cancer who seemed to benefit from adjuvant hypoxia-modifying treatment, this was not the case when the signature was used on patients with bladder cancer (12). Moreover, when comparing six of the previously published hypoxia gene signatures (10)(11)(12)(13)(14)(15) with the classifier genes in this work, we found that our genes had the strongest prognostic impact in the cervical cancer dataset (Supplementary Document S3). In particular, only the signature developed in breast cancer by Hu and colleagues (15) showed a significant association to outcome (P ¼ 0.026) in Cox PH univariate analysis.…”
Section: Discussionmentioning
confidence: 74%
“…Several hypoxia signatures have been constructed in different tissues (10)(11)(12)(13)(14)(15)(16)(17)(18), but a common cancer signature seems difficult to derive (19). The only hypoxia signature presented for cervical cancer was discovered in our previous work by combining global gene expression profiles and dynamic contrast enhanced (DCE)-MRI of the same patients (20).…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in evaluating the hypoxic status in various tissue sites, as for example in prostate cancer [24,25]. A previous study aiming at evaluating the 15-gene hypoxia classifier in patients with loco-regional gastroesophageal cancer did not give a clear answer of the applicability [26].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Moreover, in head-and-neck cancer, high tumour staining of the hypoxia marker pimonidazole correlated with inferior locoregional control, 34 and in tumour samples from patients with prostate cancer, expression of genes involved in proliferation, DNA damage repair and hypoxia correlated with both pimonidazole staining and a particularly aggressive phenotype. 35 Interestingly, a recent multi-institutional study identified and further validated an interactive influence of tumour hypoxia together with genomic instability on biochemical relapse following radical radiotherapy or prostatectomy in intermediate-risk patients. 36 Also, hypoxia-induced microRNA-210 expression has been observed in a range of experimental tumour models and patient tumour samples.…”
Section: Molecular Biomarkers Of Tumour Hypoxiamentioning
confidence: 95%